Household Accounting sebagai Upaya Pencegahan Jeratan Pinjaman Online bagi Ibu-Ibu PKK Desa Banyukambang Kabupaten Madiun - Anny Widiasmara; Apriyanti Apriyanti (Jurnal Pengabdian Masyarakat "Wiryakarya", 2026)
Poor household financial recording and planning skills can make it difficult for families to control expenses, differentiate between needs and wants, and make them vulnerable to online loan offers that are not in line with their repayment capacity. This community service activity aims to improve the understanding and skills of household accounting for PKK mothers in Banyukambang Village, Wonoasri District, Madiun Regency, as an effort to prevent the trap of illegal online loans and the use of unplanned consumer debt. The activity methods include initial observation, coordination with the village government and PKK administrators, counseling, household cash flow recording practices, monthly budgeting simulations, education on checking the legality of online loans, case discussions, and evaluations through pre- and post-tests. The main materials include recording daily income and expenses, separating needs and wants, setting priorities, emergency funds, safe debt limits, and steps to check the legality of financial services. The results of the activity show that participants [fill in actual results: for example, increased from a pre-test average of 35 to a post-test average of 75] and are able to prepare a simple family budget worksheet. This activity is expected to become a model for family financial education based on the PKK community which can be continued through regular mentoring at the Banyukambang Village level, Wonoasri District, Madiun Regency.